Енергоефективна автоматизація харчових цехів: розрахунок потужності безперебійного живлення на основі відновлювальних джерел енергії - Савченко, Марина Юріївна; Радчук, Олег Володимирович; Шевченко, Сергій Станіславович; Savchenko, Maryna; Radchuk, Oleg; Shevchenko, Serhii (Запоріжжя : Видавничий дім «Гельветика», 2026)
UA: Мета дослідження – розробити методологію визначення потужності систем безперебійного живлення (ДБЖ/NUPS) для чотирьох типових автоматизованих цехів харчової промисловості України: ковбасного, хлібопекарського, молочного та кондитерського. Наукова новизна: поєднання чотирьох елементів, які раніше не інтегрувалися в одному дослідженні в контексті України: вплив AI/IoT на пікове та середнє навантаження; оптимізація навантаження ШІ (зниження піків на 12–18 %); інтеграція гібридних ВДЕ з автономністю ≥8 год; порівняльний аналіз чотирьох цехів з акцентом на термічні процеси та автоматизацію. Методика дозволяє провести вибір середнім підприємствам (500–1000 кг/добу) гібридної системи ВДЕ+ДБЖ, знизити витрати на резервне живлення на 25–28 %, уникнути простоїв під час блекаутів (до 127 год/рік) та скоротити викиди CO2 на 42 т/рік. /// EN: Purpose. The purpose of the study is to develop a scientifically sound methodology for determining the nominal power of uninterruptible power supply systems (UPS / NUPS) for four typical automated workshops of the food industry of Ukraine – sausage, bakery, dairy and confectionery production. Originality. Scientific novelty lies in the unique combination of four elements that have not previously been integrated into a single study in the context of Ukraine: accounting for the impact of AI/IoT on peak and average load; adaptation of the Nups calculation taking into account load optimization by artificial intelligence (peak reduction by 12–18 %); integration of hybrid renewable energy systems (RES) with mandatory provision of ≥8 hours of autonomy; comparative analysis of four typical food industry workshops with emphasis on thermal processes and automation. Practical value – the developed methodology enables medium-sized enterprises (productivity 500–1000 kg/day) to reasonably select hybrid RES + UPS systems, reduce backup power costs by 25–28 %, avoid production downtime during blackouts (up to 127 hours/year in total), and cut CO₂ emissions by 42 t/year. Recommendations for scaling the solution to the food industry of Ukraine under Industry 4.0/5.0 conditions and the energy crisis are provided. Materials and research results. The article presents a comprehensive analysis of energy consumption and uninterruptible power supply requirements in automated food industry workshops integrated with renewable energy sources (RES). Four typical productions were examined: sausage, bakery, dairy, and confectionery workshops. For each, an inventory of simultaneously operating electrical equipment was compiled, considering modern automated systems (AI control, IoT sensors, robotic lines). Automation increases peak consumption by 5–10 %, but improves energy efficiency by 15–20 % through intelligent process optimization. Comparative analysis reveals that thermal processes (ovens, pasteurizers) dominate the load structure, while automated systems provide precise control and loss reduction. The maximum plant power (Nm) and the required uninterruptible power supply capacity (Nups) were calculated. Recommendations for scaling the proposed solutions to medium-sized enterprises (500–1000 kg/day) are provided.
Energy-efficient automation of food factories: calculation of uninterruptible power supply capacity based on renewable energy sources
Keywords: відновлювані джерела енергії; безперебійне живлення; автоматизація; харчова промисло- вість; електричне обладнання; renewable energy sources; uninterruptible power supply; automation; food industry; electrical equipment